WEBSITE DESIGN APPLICATIONS IN TIGER CLUB USING Macromedia Dreamweaver MX - Panji Trisnoaji (30403119) (Jurnal Sistem Informasi, 2007)
Media Information Facility is to convey a message or information that we can receive, whether oral or written, and various kinds such as newspapers, television, radio, newspapers and Computers. Internet is one medium of information very fast, and reliable keaslianya. Sexy 8 Tiger Club is the automotive club Tiger Honda owners in the South Jakarta. For media information aspirasidan Tiger Honda owners in South Jakarta. Implemebtasi can be used to Macromedia Dreamweaver MX software. So the more interesting content. With the website Sexy expected 8 Tiger Club Tiger Honda owners in South Jakarta to obtain information and to channel their aspirations.